2008
DOI: 10.3138/cja.27.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Personnes âgées et perception des risques en matière de conduite automobile: les conducteurs âgés manifestent-ils encore de l'optimisme comparatif?

Abstract: People frequently express comparative optimism ; that is, they believe they are less likely than average to experience negative events. The aim of the present study is, first, to observe whether people of more than 65 years are still optimists when they evaluate driving-related risks; and second, to test the assumption that older drivers show less optimism when they compare themselves with average-age drivers than when they compare themselves with same-age drivers. Our results reveal that drivers of more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…When older drivers are asked to compare themselves with drivers of different age groups, they continue to show-comparable to the other age groups-an optimistic bias indicating that they have better driving skills and lesser accident risks than other drivers of the same age group or of younger age groups (Gosselin et al 2010;Spitzenstetter and Moessinger 2008). Such a selfserving bias aims at the reduction of anxiety and the maintenance of self-confidence and it also suggests that negative stereotypes about older drivers do not completely alter their driving self-confidence.…”
Section: Awareness Of Age-related Changes and Coping With Driving-relmentioning
confidence: 99%
“…When older drivers are asked to compare themselves with drivers of different age groups, they continue to show-comparable to the other age groups-an optimistic bias indicating that they have better driving skills and lesser accident risks than other drivers of the same age group or of younger age groups (Gosselin et al 2010;Spitzenstetter and Moessinger 2008). Such a selfserving bias aims at the reduction of anxiety and the maintenance of self-confidence and it also suggests that negative stereotypes about older drivers do not completely alter their driving self-confidence.…”
Section: Awareness Of Age-related Changes and Coping With Driving-relmentioning
confidence: 99%
“…Though unrealistic optimism appears to be a robust phenomenon and has been demonstrated across a wide variety of events (Perloff & Fetzer, 1986) and samples (Spitzenstetter & Moessinger, 2008), some research supports the notion optimistic bias could be moderated by personal experience (Burger & Palmer, 1992;Helweg-Larsen & Shepperd, 2001). Individuals who have already been confronted with a negative event tend to feel less optimistic compared to others when they evaluate their risk of being again confronted with this kind of event (van der Velde, Hooykaas, & van der Pligt, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have revealed the phenomenon of comparative optimism (CO), that is the tendency of people to consider that they are less likely than the average person to experience negative events and more likely to experience positive events (Harris & Middleton, ; Weinstein, ). CO appears to be a robust phenomenon and has been demonstrated across a wide variety of outcomes (Aucote & Gold, ; Campbell, Greenauer, Macaluso, & End, ; Svenson, ) and samples (Rose, Endo, Windschitl, & Suls, ; Spitzenstetter & Moessinger, ). Within the different explanations posited for CO, evidence supports a self‐presentational motivation .…”
mentioning
confidence: 99%